Density, diversity and community composition of trees in tropical thorn forest, peninsular India - Evitex-Izayas, J.; Udayakumar, M. (Current Botany, 2021)
Tropical thorn forests (TTFs) are characterized by the presence of small and thorny trees which usually shed their leaves in dry season. A quantitative phytosociological study was conducted in Uthumalai Reserve Forest of Peninsular India to record density, species richness, diversity and population structure of trees. Diameter of all free standing trees ≥1 cm diameter at breast height (DBH, cm) was measured at 1.37 m above the ground. A sum of 4135 trees ≥1cm DBH recorded from one hectare study plot. With 2272 (54.94%) individuals Dalbergia spinosa dominated the study plot followed by Commiphora berryi (484, 11.70%), Grewia flavescens (259, 6.26%), Dichrostachys cinerea (206, 4.98%) and Anogeissus pendula (171, 4.14%). In total, 26 species belonged to 19 genera and 15 families found in one ha study plot. The family Mimosaceae had a large number of species followed by Apocynaceae, Capparidaceae, Tiliaceae, Rhamnaceae. Rubiaceae (each 2 species). Stand basal area of tree community recorded as 15.238 m2 ha-1. Commiphora berryi constituted 50.80% (7.74 m2 ha-1) of stand basal area followed by Dalbergia spinosa (19.43%, 2.96 m2 ha-1). The forest showed a reverse J shaped population structure. Shannon diversity (H), equitability (H’) and Simpson’s dominance (D) indices of study area recorded as 1.76, 0.54 and 0.335, respectively. Dalbergia spinosa, Commiphora berryi, Grewia flavescens, Dichrostachys cinerea and Anogeissus pendula topped the species important value index with 87.80, 73.53, 20, 19.79, 17.43 scores, respectively. In family important value index, Papilionaceae topped the list followed by Burseraceae and Mimosaceae with scores 129.32, 74.23 and 34.43, respectively. The study area endowed with a moderate species richness and diversity, and acts as one of the homes for an IUCN’s vulnerable tree species.